Wing geometric morphometrics as a tool for taxonomic identification of two fly species (Diptera: Muscidae) of forensic relevance - Nuñez, José Antonio (2019)
The taxonomic identification of fly species through wing geometry is a helpful tool for entomologists and officials involved in forensic research, who not necessarily require expertise on insect taxonomy. Members of the Muscidae family are relevant sources of evidence in forensic entomology; however, developing countries often lack experts in the taxonomical identification of essential species for the assessment of aspects such as the minimum postmortem interval (mPMI). Our study proposes a low-cost, fast, and technologically-accessible quantitative tool for the identification of Atherigona orientalis and Ophyra aenescens, associated with human corpses at advanced states of decomposition. We propose a tool that is based on the geometric variability observed in eight homologous landmarks on wing veins and the interpretation of morphometric estimates after a generalized Procrustes analysis. The use of a geometric approach for effective discrimination between Atherigona orientalis and Ophyra aenescens was supported by statistically significant differences in wing conformation and size. The evidence presented in this study shows that the analysis of geometric variability in the wing morphology of species of forensic relevance can contribute to simple and objective species identification. Geometric morphometrics is a simple and readily available tool for forensic science.